Factors that Affecting Behavior Change - Jandaeng, Burachat; Kosolkittiamporn, Saowaluk; Kenaphoom, Sanya (Dhammathas Academic Journal, 2019)
Behavioral science is the study of human behavior related to behavior in society. To analyze the causes that make human choices to act on things, both externally manifested clearly. Thoughts, beliefs, attitudes, and behavioral sciences, psychology, social psychology, sociology, anthropology, economics, and psychology have been used in a variety of disciplines. Issues of interest in individual science. The factors many affecting behavior change.